Studi Komparasi Bacaan Riwayat Qalun dan Riwayat Hafs Q.S. al-Fatihah, al-Baqarah, dan Ali Ã¢â‚¬ËœImran - Fathoni, Ahmad (Lajnah Pentashihan Mushaf Al-Qur'an, 2012)
This paper discusses significant differences between the reading ofÃ‚Â the Qalun narration and that of Hafs in the Qur Ã¢â‚¬â„¢an, chapter al-FÃ„Âtihah, al-Baqarah, and'Ali Imran, and are described in a comparative format between both of them according toÃ‚Â tarÃ„Â«q ash-ShaÃ‚Â¯ibiyyah.Ã‚Â The study found different readings:Ã‚Â mÃ„Â«mjamaÃ¢â‚¬Ëœ,Ã‚Â idgÃ„ÂmÃ‚Â Ã‚Â¡agÃ„Â«rÃ‚Â andÃ‚Â hÃ„ÂÃ¢â‚¬â„¢Ã‚Â kinÃ„ÂyahÃ‚Â (in certain places), twoÃ‚Â hamzahsÃ‚Â in one word, twoÃ‚Â hamzahsÃ‚Â in two words, the wordÃ‚Â Ã¯Âºâ€Ã¯Â¯Â¾Ã˜Â±Ã¯Â»Â®Ã¯ÂºËœÃ¯Â»Å¸Ã˜Â§,Ã‚Â yaÃ¢â‚¬â„¢Ã‚Â iÃ‚Â«Ã„ÂfahÃ‚Â (additionalÃ‚Â yaÃ¢â‚¬â„¢), and yÃ„ÂÃ¢â‚¬â„¢ zÃ„Â`idah (additional yaÃ¢â‚¬â„¢). The findings of the words which are included in the special ruleÃ‚Â (al-farsyÃ‚Â Ã‚Â¥urÃ…Â«f)Ã‚Â are located in 113 places, with details of the places as follow: one place in Surah al-Fatihah, 64 places in Surah al-Baqarah, and 48 places in Surah Ali 'Imran.